1999
DOI: 10.4319/lo.1999.44.6.1522
|View full text |Cite
|
Sign up to set email alerts
|

Crevices as refugia for stream diatoms: Effect of crevice size on abraded substrates

Abstract: This study explored the mechanisms by which crevices act as refugia for small algae during abrasive disturbances. Four substrates with different crevice features were subjected to three levels of abrasion in a stream-based experiment. Substrates were sand-grain caddisfly cases and three glass rod substrates that mimicked caddisfly cases in size and shape, as well as forming a gradient of larger crevices (i.e., smooth with no crevices, sanded with shallow pits, and scratched with deeper grooves). Substrates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 65 publications
3
42
0
1
Order By: Relevance
“…Bergey (1999) showed that small crevices on rough surfaces are used by the diatoms as refuge against water waves and grazer pressure, resulting in more intensive development of periphyton on less smooth surfaces. Hart (1978), Clifford et al (1989) and Bergey (1999) noted that small aquatic organisms and detrital particles accumulate in depressions on rough surfaces which result in greater diversity and abundance of macroinvertebrates. Thus, an increase in food resources can be a key factor in more numerous occurrences of both predator and parasite leeches.…”
Section: Discussionmentioning
confidence: 99%
“…Bergey (1999) showed that small crevices on rough surfaces are used by the diatoms as refuge against water waves and grazer pressure, resulting in more intensive development of periphyton on less smooth surfaces. Hart (1978), Clifford et al (1989) and Bergey (1999) noted that small aquatic organisms and detrital particles accumulate in depressions on rough surfaces which result in greater diversity and abundance of macroinvertebrates. Thus, an increase in food resources can be a key factor in more numerous occurrences of both predator and parasite leeches.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the deposition of algae within the crevices is due to the accumulation of debris in them and the possible establishment of refuges (Bergey, 1999;Nowell and Jumars, 1984;Davis and Barmuta, 1989;Snelgrove et al, 1993). In the present study we tested surfaces with crevice sizes greater than previous studies (with periphytic community) considering that macroalgae would require larger crevices to get refuge, as reported for larger diatoms (Bergey, 1999). Actually, we found macroalgae within the crevices, but the shapes and dimensions used seemed to be insufficient and then limiting the growth of these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, investigating crevices size as refugia for diatoms, Bergey (1999) found that larger crevices had a better protection for larger algae. As macroalgae have a greater size and no experimental investigation focusing on influence of crevice size on development of this algal community was yet conducted, we carried out the present study to investigate the colonization and the establishment of macroalgal community on surfaces with milimetric crevices, a scale slightly higher than previous investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In lotic ecosystem, the higher proportion of algae firmly adhered to surface roughness can suggest the community resistance to scouring (Murdock and Dodds, 2007). The physical properties can have effects on resistance and resilience of the algal community in the face of environmental perturbations (Bergey, 1999, …”
Section: Discussionmentioning
confidence: 99%
“…The topography of the microhabitat is defined by irregularities on the substrate surface (depressions, crevices and protrusions), which may influence biomass accumulation (Johnson, 1994), cell adhesion (Sekar et al, 2004) and algae susceptibility to grazing and scouring (Bergey, 1999, Bergey andWeaver, 2004). The surface irregularities can also minimize water flow action around the substrate, modifying the diffusion boundary layers (De Nicola andMcIntire, 1990, Dodds andBiggs, 2002).…”
Section: Introductionmentioning
confidence: 99%